Neopedies taimensis n. sp. of Brazilian Dichroplini (Orthoptera: Acrididae, Melanoplinae) from Rio Grande do Sul, Brazil - Da Costa, Maria Kátia Matiotti; Acosta, Riuler Corrêa; Timm, Vítor Falchi; Zefa, Edison (Zootaxa, 2021)
Neopedies taimensis n. sp. is described as a new species of grasshopper from the genus Neopedies Hebard, 1931 collected in Taim Ecological Station, State of Rio Grande do Sul, Brazil. This description is supported with photographs that detail the male and female external and internal morphological characteristics. The new species differs from the other species known by furculae developed and sclerotized, epiproct with two protuberances, cerci quadrangular indented and sclerotized, ancorae developed and lophi with posterior projections divergent. In addition, we present habitat notes, geographic distribution, key to the species of genus and chromosome complement. Chromosome analyses were performed using standard staining procedures, showing diploid number of 2n = 23, X0♂/24, XX♀ and the karyotype made up of exclusively acrocentric chromosomes.